PENDIDIKAN PENTINGNYA MENABUNG SEJAK DINI DAN MEMBERIKAN UANG BANK KEPADA ANAK TPQ AS-SHOLIHIN (Journal Edutama Multidisciplinary Indonesian, 2024)
Earl financial management is one of the important aspect to prepare for a bright future, including throught saving habit. Based on observasion made y TPQ As-Sholihin, Padukuhan Pasekan Kidul Balectur it was found that many children ddidn’t understand the important of saving. This services ctivity aims to increase children understanding of the benefits of saving and train them to manage their finances wisely.The methods used include observation, emotional approach through Qur’an recitation activities materi, material delivery through inspirational stories, discussion and giving unique money banks. The resut of this activity showed an increase in childrens interest in saving and discipline in financial management. The provision of money banks is also proven to motivate children to reduce buy snack and save money. This education is expected to foster good habits in the next generation and strengthen the relationship between KKN students and TPQ As-Sholihin children.